Alloyed Crystalline CdSe1‐xSx Semiconductive Nanomaterials – A Solid State 113Cd NMR Study. Issue 10 (12th October 2020) - Xing, Baoyan; Ge, Sai; Zhao, Jianguo; Yang, Hui; Song, Jie; Geng, Yu; Qiao, Yuying; Gu, Ling; Han, Peide; Ma, Guibin
Abstract: Solid‐state NMR analysis on wurtzite alloyed CdSe1−x Sx crystalline nanoparticles and nanobelts provides evidence that the 113 Cd NMR chemical shift is not affected by the varying sizes of nanoparticles, but is sensitive to the S/Se anion molar ratios. A linear correlation is observed between 113 Cd NMR chemical shifts and the sulfur component for the alloyed CdSe1−x Sx (0Cd =169.71⋅XS +529.21). Based on this correlation, a rapid and applied approach has been developed to determine the composition of the alloyed nanoscalar materials utilizing 113 Cd NMR spectroscopy. The observed results from this system confirm that one can use 113 Cd NMR spectroscopy not only to determine the composition but also the phase separation of nanomaterial semiconductors without destruction of the sample structures. In addition, some observed correlations are discussed in detail. Abstract : Finding the right composition : The 113 Cd NMR chemical shifts of anion rich alloyed CdSe1−x Sx materials are not affected by the nanoparticle size, but do change depending on the bound anion about the Cd(II) cation. Based on this correlation, a rapid and easy approach to determine the composition of the alloyed nanoscale materials has been developed by utilizing 113 Cd NMR spectroscopy.